Physicochemical, technofunctional, in vitro antioxidant, and in situ muscle protein synthesis properties of a sprat (Sprattus sprattus) protein hydrolysate - Shekoohi, Niloofar; Naik, Azza Silotry; Amigo-Benavent, Miryam; Harnedy-Rothwell, Pádraigín A.; Carson, Brian P.; FitzGerald, Richard J. (Frontiers in Nutrition, 2023)
Sprat (Sprattus sprattus) is an underutilised fish species which may act as an economic and sustainable alternative source of protein due to its good amino acid (AA) profile along with its potential to act as a source of multiple bioactive peptide sequences. This study characterised the physicochemical, technofunctional and in vitro antioxidant properties along with the AA profile and score of a sprat protein enzymatic hydrolysate (SPH). Furthermore, the impact of the SPH on the growth, proliferation and muscle protein synthesis (MPS) in skeletal muscle (C2C12) myotubes was examined. The SPH displayed good solubility and emulsion stabilisation properties while containing all essential and non-essential AAs. Limited additional hydrolysis was observed following in vitro simulated gastrointestinal digestion (SGID) of the SPH. The SGID-treated SPH (SPH-SGID) displayed in vitro oxygen radical antioxidant capacity (ORAC) activity (549.42 µmol TE/g sample) and the ability to reduce (68 %) reactive oxygen species (ROS) production in C2C12 myotubes. Muscle growth and myotube thickness were analysed using an xCelligence™ platform in C2C12 myotubes treated with 1 mg protein equivalent.mL-1 of SPH-SGID for 4 h. Anabolic signaling (phosphorylation of mTOR, rpS6 and 4E-BP1) and MPS (measured by puromycin incorporation) were assessed using immunoblotting. SPH-SGID significantly increased myotube thickness (p<0. 0001) compared to the negative control (cells grown in AA and serum free medium). MPS was also significantly higher after incubation with SPH-SGID compared with the negative control (p<0. 05). These preliminary in situ results indicate that SPH may have the ability to promote muscle enhancement. In vivo human studies are required to verify these findings.